Templer and the road to Malayan independence : the man and his time / Leon Comber - Comber, Leon (ISEAS, 2015)
Provides an account of General Templer's administration in Malaya as High Commissioner and Director of Operations (1952-54) during the Malayan Emergency. It departs from the usually accepted orthodox assessment of his time in Malaya by focusing on the political and socio-economic aspects of his governance rather than the military.